Decline in incidence of hospitalisation for acute myocardial infarction in the Netherlands from 1995 to 2000. Issue 2 (29th April 2005) - Koek, H L; de Bruin, A; Gast, A; Gevers, E; Kardaun, J W P F; Reitsma, J B; Grobbee, D E; Bots, M L
Abstract : Objective: To study the change in incidence of hospitalisation for a first acute myocardial infarction (AMI) in the Netherlands from 1995 to 2000. Methods: Patients hospitalised with their first AMI in the Netherlands in 1995 and 2000 were identified through linkage of the national hospital discharge register and the population register. Results: 21 565 patients hospitalised for their first AMI in 1995 and 19 058 patients hospitalised for their first AMI in 2000 were identified. In both years, the age specific incidence of hospitalisation for a first AMI was higher in men than in women and increased with age (up to 90 years). In both men and women, the age standardised incidence was lower in 2000 than in 1995, a decline of 19% (95% confidence interval 17% to 21%) and 17% (95% confidence interval 14% to 19%), respectively. Conclusions: Our study provides the first nationwide incidence estimates of first AMI in the Netherlands. From 1995 to 2000, the risk of AMI declined considerably.